Хищники и охотничье хозяйство - Кистяковский, А.Б. (Вестник зоологии, 1971)
Carruvora, though being the factors of selection, do not favour the flourishing of
the population of their preys, because they exterminate temporarily weak but valuable
Individuals. When there is a considerable amount of Carnivora they stop the growth of
"the prey's population quantity and sometimes lead to their complete disappearance. II is
•expedient to replace the selective role of Carnivora by the selection occuring during ordinary hunting as well as by a special selective shooting of animals.